Mechanism of formation of competitiveness of non-Olympic sports - Середа, Наталія (Slobozhanskyi Herald of Science and Sport, 2019)
Nataliiya Sereda The article analyzes the competitiveness of non-Olympic sports in Kharkiv. A mechanism for the formation of competitiveness non-Olympic sports are proposed. Purpose: develop a mechanism for the formation of competitiveness of non-Olympic sports. Material & Methods: analysis of literary sources and documents, questioning, organizational modeling, methods of marketing analysis (SWOT-analysis), expert assessment, methods of mathematical statistics. The research was conducted in 5 sports schools in Kharkiv, where non-Olympic sports are cultivated. In total, 136 people participated in the study. The composition of the respondents included: directors, deputy directors, methodologists, trainers. Results: on the basis of marketing analysis, the mechanism of formation of competitiveness of non-Olympic sports was revealed. Conclusions: as a result of the study, information on the formation of the competitiveness mechanism for non-Olympic sports has been summarized. A competitiveness mechanism was developed for non-Olympic sports and the effectiveness of the developed mechanism was confirmed using the method of expert assessments